Genomic glucocorticoid action in embryonic mouse neural stem cells. (1st March 2023) - Berry, Kimberly J.; Chandran, Uma; Mu, Fangping; Deochand, Dinesh K.; Lei, T.; Pagin, Miriam; Nicolis, Silvia K.; Monaghan-Nichols, A. Paula; Rogatsky, Inez; DeFranco, Donald B.
Abstract: Prenatal exposure to synthetic glucocorticoids (sGCs) reprograms brain development and predisposes the developing fetus towards potential adverse neurodevelopmental outcomes. Using a mouse model of sGC administration, previous studies show that these changes are accompanied by sexually dimorphic alterations in the transcriptome of neural stem and progenitor cells (NSPCs) derived from the embryonic telencephalon. Because cell type-specific gene expression profiles tightly regulate cell fate decisions and are controlled by a flexible landscape of chromatin domains upon which transcription factors and enhancer elements act, we multiplexed data from four genome-wide assays: RNA-seq, ATAC-seq (assay for transposase accessible chromatin followed by genome wide sequencing), dual cross-linking ChIP-seq (chromatin immunoprecipitation followed by genome wide sequencing), and microarray gene expression to identify novel relationships between gene regulation, chromatin structure, and genomic glucocorticoid receptor (GR) action in NSPCs. These data reveal that GR binds preferentially to predetermined regions of accessible chromatin to influence gene programming and cell fate decisions. In addition, we identify SOX2 as a transcription factor that impacts the genomic response of select GR target genes to sGCs (i.e., dexamethasone) in NSPCs. Highlights: Most accessible chromatin regions are H3K27ac + transcriptional enhancers. Dex does not drastically change the chromatin landscape of NPSCs. Dex increases GR binding, mostly within accessible chromatin, by 236% in NSPCs . GR and SOX2 interact to coordinate the genomic response to sGCs in-vitro. SOX2 may be involved in the etiology of sGC-associated neurodevelopmental deficits.